Program Gerbang Desa Saburai dan Pengentasan Desa Tertinggal Di Provinsi Lampung - Ambya Ambya (Journal of Food System & Agribusiness, 2020)
This study aims to evaluate and analyze the Saburai Village Gate Program implemented by the Lampung provincial government in 2015-2018 with the aim of alleviating underdeveloped villages. This program is expected to be a model for improving the status of the village based on empowerment. The method used in this research is panel data analysis using significance tests, and the Random Effect Model (REM) is the best model to use. The results obtained show that the variable of community direct assistance and non-government funding has a negative and significant effect on the number of disadvantaged villages. Where the increase in direct assistance from communities and non-governmental organizations is able to reduce the number of underdeveloped villages. In the future, this model can be developed as a tool of local government policy in order to improve public services by providing rural infrastructure.Keywords:  Community Direct Aid, Self-Help Funds, Random Effect Model.